The Contribution of Local Wisdoms with in Sundanese Hymns in Constructing Mental and Spiritual Strength of Superior Human Resource to Create a Corruption-Free Indonesia - Hikmawati, Fenti (International Journal of Psychosocial Rehabilitation, 2020)
One of the biggest problems in Indonesia is corruption. Many regulations were issued as efforts to overcome it. This research aims to find out the role of local wisdom within Sundanese hymns in constructing mental and spiritual strength ofsuperior human resource and its contribution in creatinga corruption-free Indonesia. The data of this research were taken from Ahmad Sujai‟s Arabic and Sundanese anthology from the priangan culture of West Java. The methods used in this research were an observation, interview, and documentary study ofa Arabic book entitled Irsyadul „Awam Ila Sabilis Salam. We found that corruption is conducted by an individual or a group from any level of society. Corruption deviates from any rule of law, religion, as well as norms. Local wisdom in the form of Sundanese hasa psychological and therapeutic effect as a counselling guidance to embed a nobility of soul, achieve noble values, think brilliantly, know God, carry out His orders and avoid His prohibition, become His lover, believe in God as The Protector, not become narrow-minded, wish for His blessings, live in simplicity and avoid destructive behaviors, such as being greedy and corruption. Therefore, we recommend that empowering local wisdom through Sundanese hymns, early and massively, might have a positive implication in preventing corruption in any sectors of life.